Q08 Potential neuroprotective effects of pridopidine in Huntington's disease. (29th August 2012) - Di Pardo, A; Alberti, S; Maglione, V; Amico, E; Squitieri, F
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disorder characterised by hyperkinetic movements (chorea), cognitive and psychiatric dysfunction. The disease is caused by an expanded polyglutamine stretch in huntingtin (Htt). mHtt interferes with different cellular functions increasing susceptibility of neurons to apoptosis, which ultimately results in neurodegeneration of the striatum and cortex. Recent evidence indicates that dopamine signalling is also impaired in HD, suggesting dopaminergic circuitry may be a potential therapeutic target for this disease. The dopaminergic stabiliser pridopidine belongs to a new family of compounds known as dopidines, and is in development for treatment of motor symptoms associated with HD. In Phase IIb and III clinical trials, pridopidine has been shown to improve overall motor function in patients with HD. However, it is not known whether the molecule may exert a neuroprotective effect in brain cells. Aims: To evaluate the potential neuroprotective effect of pridopidine in HD, by investigating whether pridopidine plays a role in the regulation of molecular mechanisms essential for neuronal cell survival. Methods: We performed in vitro experiments in mouse striatal-derived cells expressing mutant Htt (SThdh111/111) and evaluated cell survival in the presence and absence of pridopidine. SThdh111/111 cells were cultured in apoptotic conditions (serum starvation and/or quinolinic acid), in the presence or absence of pridopidine. Cell survival was detected by Annexin V staining. Results: Preliminary results indicate that pridopidine protects cells from apoptosis and induces an increase in phosphorylation of the protein kinase ERK1/2, whose activation has been shown to be protective in several HD models. Conclusions: These findings support the hypothesis that pridopidine exerts a neuroprotective effect in HD models and prompt us to further investigate its potential therapeutic use in HD.